EFFECTS OF ELECTROMAGNETIC RADIATION FROM MOBILE PHONES AND CASE STUDIES OF COMPUTATIONAL MODELS FORCALCULATING SAR DISTRIBUTION IN HUMAN BODY - Settapong Malisuwan; Wassana Kaewphanuekrungsi (International Journal of Innovations in Engineering Research and Technology, 2021)
Nowadays, the utilization of mobile wireless devices has been rapidly widespread, mobile phones in particular. The manufacturers of mobile wireless devices must ensure that the level of energy emitted from their products will not exceed the threshold frequency. This paper aims to review and introduce the effects of electromagnetic radiation and case studies of computational models for calculating SAR distribution in human body.